Analysis on Laterally Loaded Group Piles by Plaxis 3D Foundation - Dewi, Sri; Liong, Gouw Tjie (ComTech: Computer, Mathematics and Engineering Applications, 2011)
It has been known that a group pile lateral capacity is smaller than the sum of each pile capacity composing the group. A reduction factor, also known as efficiency factor, is required to determine the effective lateral capacity of group piles. To the authors? knowledge, in most geotechnical text books, only the spacing of piles is considered in evaluating the pile group lateral capacity. No consideration on the effects of soil stiffness modulus and the total number of piles forming the group is taken into account. This research tried to investigate the influence of those factors by using geotechnical 3D finite element software, namely Plaxis 3D foundation. It is found that the bigger the number of piles in a group, the lower the efficiency factor is; the higher the soil stiffness modulus, the greater the efficiency is.